Menjadi Kreator Digital: Menumbuhkan Pola Pikir Kewirausahaan yang Adaptif Melalui Penggunaan Teknologi Digital - Arissaputra, Rivaldi; Maisa Azizah Asmara; Winda Gafrilia Prianka; Dhenahi Jerfiani Wendiyana (Politeknik Piksi Ganesha Indonesia, 2026)
The Indonesian diaspora community in Malaysia, particularly members of Pimpinan Cabang Istimewa Muhammadiyah (PCIM) and Pimpinan Cabang Istimewa 'Aisyiyah (PCIA) Malaysia, faces limited understanding of digital products as tools for supporting adaptive economic activities within a multicultural environment. This community service activity aimed to strengthen the adaptive entrepreneurial mindset through enhanced understanding of digital products among the PCIM-PCIA Malaysia community. The program was implemented using a community-based, educative, and participatory counseling method, involving 20 purposively selected participants from PCIM and PCIA Malaysia members. Program effectiveness was measured using a pre-test and post-test design covering ten indicators of digital product understanding. Evaluation results demonstrated a significant improvement across all indicators, with average pre-test scores ranging from 2.10 to 3.10 increasing to 4.15 to 5.00 on a five-point scale following the intervention. The most notable gains were recorded in the Definition of Digital Products indicator (2.25 to 5.00) and the Practical Application of Digital Products in Daily Economic Activities indicator (3.10 to 4.95). These findings affirm that a structured, contextually grounded, and participatory counseling approach is effective in enhancing digital product literacy and strengthening the foundation of an adaptive entrepreneurial mindset within diaspora communities. It is recommended that the program be further developed through practical training, digital platform simulation, and ongoing mentoring to ensure the sustainability of the outcomes achieved.